First insights into clinical and resistance features of infections by Klebsiella pneumoniae among oncological patients from a referral center in amazon region, Brazil - Santos, Anderson Lineu Siqueira dos (MDPI, 2021)
Abstract: Klebsiella pneumoniae appears as one of the most prevalent pathogens among cancer patients. The present study investigates the clinical, epidemiological and microbiological aspects related to infections caused by K. pneumoniae in cancer patients treated at an oncology referral center in the state of Par?, Amazon region, Brazil. Between July 2017 to July 2019, an epidemiological, observational, cross-sectional study, with a descriptive and analytical approach was conducted, including patients with confirmed diagnosis of cancer who acquired infection by K. pneumoniae 72 h after hospital admission. K. pneumoniae isolates included in the study were obtained from different clinical materials (blood, urine, catheter tip and bladder catheter, orotracheal secretions, oncological and surgical wounds). Antimicrobial susceptibility testing and molecular detection of the carbapenemase-encoding genes were performed. A high prevalence of MDR K. pneumoniae isolates was observed, including two colistin-resistant isolates and seven isolates harboring blaKPC-1 gene. To conclude, our findings provide the firsts insights into the epidemiology and infection by K. pneumoniae in the state of Par?, Brazil, and may be useful on treatment guidance and establishment of strategies to control the spread of resistance strains of K. pneumoniae in the region.